2009
DOI: 10.1093/hmg/ddp520
|View full text |Cite
|
Sign up to set email alerts
|

Sox10 gain-of-function causes XX sex reversal in mice: implications for human 22q-linked disorders of sex development

Abstract: Male development in mammals is normally initiated by the Y-linked gene Sry, which activates expression of Sox9, leading to a cascade of gene activity required for testis formation. Although defects in this genetic cascade lead to human disorders of sex development (DSD), only a dozen DSD genes have been identified, and causes of 46,XX DSD (XX maleness) other than SRY translocation are almost completely unknown. Here, we show that transgenic expression of Sox10, a close relative of Sox9, in gonads of XX mice re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
130
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(139 citation statements)
references
References 60 publications
4
130
0
5
Order By: Relevance
“…Serial sagittal sections (,5 mm in thickness) were cut in the middle portion including the largest area and then every 10th section of the samples was principally analyzed by anti-SOX9 immunostaining, while adjacent section was used for immunostaining for other markers as described below. The sections were incubated with anti-AMH (1:200 dilution; Santa Cruz), anti-laminin (1:400 dilution; ICN Pharmaceuticals), anti-BrdU (1:100 dilution; Dako Cytomation), anti-DMRT1 (1:100 dilution; Santa Cruz), anti-FOXL2 [1:200 dilution (Uda et al, 2004); 1:200 dilution (goat antibodies for double-staining with SOX9), Abcam], anti-heparan sulfate (1:200 dilution; 10E4 epitope; Seikagaku Corporation, Japan), anti-MVH/DDX4 (1:5,000 dilution) (Toyooka et al, 2000), anti-PCNA (1:1,000 dilution; PC10; DAKO), anti-SF1/Ad4Bp [1:1,000 (Ikeda et al, 2001)], anti-SOX9 [1:250 dilution Kent et al, 1996;Polanco et al, 2010)], anti-SPRR2d (1:300 dilution; Alexis Biochemicals), or anti-SRY [1:10 dilution (Wilhelm et al, 2005)] at 4˚C for 12 hours. The reaction was visualized with biotin-conjugated secondary antibody in combination with Elite ABC kit (Vector Laboratories) or by Alexa-Fluor-488/594-conjugated secondary antibodies (Invitrogen).…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%
“…Serial sagittal sections (,5 mm in thickness) were cut in the middle portion including the largest area and then every 10th section of the samples was principally analyzed by anti-SOX9 immunostaining, while adjacent section was used for immunostaining for other markers as described below. The sections were incubated with anti-AMH (1:200 dilution; Santa Cruz), anti-laminin (1:400 dilution; ICN Pharmaceuticals), anti-BrdU (1:100 dilution; Dako Cytomation), anti-DMRT1 (1:100 dilution; Santa Cruz), anti-FOXL2 [1:200 dilution (Uda et al, 2004); 1:200 dilution (goat antibodies for double-staining with SOX9), Abcam], anti-heparan sulfate (1:200 dilution; 10E4 epitope; Seikagaku Corporation, Japan), anti-MVH/DDX4 (1:5,000 dilution) (Toyooka et al, 2000), anti-PCNA (1:1,000 dilution; PC10; DAKO), anti-SF1/Ad4Bp [1:1,000 (Ikeda et al, 2001)], anti-SOX9 [1:250 dilution Kent et al, 1996;Polanco et al, 2010)], anti-SPRR2d (1:300 dilution; Alexis Biochemicals), or anti-SRY [1:10 dilution (Wilhelm et al, 2005)] at 4˚C for 12 hours. The reaction was visualized with biotin-conjugated secondary antibody in combination with Elite ABC kit (Vector Laboratories) or by Alexa-Fluor-488/594-conjugated secondary antibodies (Invitrogen).…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%
“…We overexpressed Dmrt1 in XX mouse fetal gonads using a Wt1-BAC transgene system (Polanco et al, 2010;Zhao et al, 2014a). Surprisingly, ectopic expression of Dmrt1 was sufficient to drive testicular differentiation at the fetal stage and male secondary sex development postnatally.…”
Section: Introductionmentioning
confidence: 99%
“…1A) (Zhao et al, 2014a). Using this enhancer, we have previously demonstrated that the transgene of interest is specifically expressed in XX and XY gonadal somatic pre-supporting cells, and not in the mesonephros, beginning at 10.5 days post coitum (dpc) (Polanco et al, 2010), before sex determination takes place.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of both Ovotesticular and Testicular-DSD in families, especially in identical twins, indicates them as different manifestations of the same disorder of gonadal development (15)(16)(17). In the absence of SRY gene, the up-regulation or super-expression of some members of SOX family (Sry-related HMG-box) have been proposed as involved in XX male etiology (18)(19)(20). The diagnosis of SRY-negative testicular-DSD can be done in childhood upon investigation of ambiguous genitalia and gynecomastia.…”
Section: Introductionmentioning
confidence: 99%